Routine outcomes to investigate differences between ethnic minorities and White British people presenting to emergency services for injury: the stakeholder consultation - Fadi Baghdadi; Bridie Angela Evans; Ann John; Adam Lloyd; Ronan A Lyons; Gargi Naha; Alison Porter; Aloysius Niroshan Siriwardena; Helen Snooks; Alan Watkins; Julia Williams; Ashrafunnesa Khanom (Health and Social Care Delivery Research)
Introduction Research has found differences in processes and outcomes of care between people in ethnic minorities and White British populations in some clinical conditions, although findings have been mixed. The Building an understanding of Ethnic minority people’s Service Use Relating to Emergency care for injuries study is investigating differences in presentation, experience and health outcomes between people from ethnic minorities and White British people who seek emergency health care for injury. Objective Our aim was to consult with stakeholders to define measurable outcomes available in routine ambulance and emergency department data; to assess the appropriateness of existing outcome measures for ethnic minorities and White British people; and to identify any gaps. Method Clinicians, public contributors, researchers, people from the third sector, public health, healthcare inclusion were invited to join an online workshop to discuss routine outcomes. Results Twenty participants attended the stakeholder consultation, with only one being a public contributor, a limitation. Eleven were from a minority ethnic background and seven were female. The integrated list of outcomes included 25 items, combining routine outcomes from the Building an understanding of Ethnic minority people's Service Use Relating to Emergency care for injuries protocol and literature (n = 17) with additional outcomes (n = 8). Notably, the initial list lacked provisions for safeguarding referrals and cases of treatment refusal, which were new additions. Safety concerns arose due to the lack of safeguarding referrals, treatment refusal and self-discharge. Factors such as pre-existing health conditions, injury location and experiences of discrimination were identified as possible influences on care quality and waiting times for ethnic minority patients. Conclusion Although the number of stakeholders taking part in our consultation was low, their participation identified outcomes not found in routine data, supporting the adoption of a mixed-methods approach to answer our research questions. A future consultation could look to include more public members and wider range of clinicians including those who work in safeguarding and rehabilitation services. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number NIHR132744. Plain language summary Research has shown that people from ethnic minorities often have less favourable healthcare experiences and outcomes than white British people. Our BE SURE study aims to establish whether there are differences between these groups and whether this can be seen in routinely available health outcome data or through patients’ own words through questionnaires and interviews. Before starting data collection, we wanted to consult with people who may deliver or receive emergency health care for injuries, about what routinely available healthcare measures and outcomes we should include in the study. Twenty stakeholders joined the meeting: clinicians, paramedics, researchers and representatives from healthcare organisations, the third sector and a public contributor. We firstly explained what the study was about, and what we hoped to achieve during the online consultation meeting. We presented examples of measurable outcomes that we had included in our original research proposal for injuries. We broke into small groups to discuss these outcome measures and identify gaps. We also asked for comments and suggestions to check the appropriateness of these measures. Participants agreed that the proposed measures were mostly appropriate; these included tests, treatments, waiting times, referrals to other doctors, leaving the hospital against medical advice and time spent in the emergency department. They identified two new outcomes, which were safeguarding referrals and refusal of treatment. The final agreed list of outcomes was 25. Participants also discussed disparities in medication and treatments provided to ethnic minorities compared to white British people, such as pain relief. Additionally, they explored various factors that could affect care differently across these groups. For instance, ethnic minorities may experience discrimination, have distinct health issues or experience variations in the location, nature and severity of injuries. These factors could influence waiting times, pain management and overall quality of care.